An Environmental Model for Performance Measurement in Multi-Outlet Businesses - Kinney, William R. (Journal of Accounting Research, 1969)
Standards for evaluating the performance of outlet managers in companies with numerous outlets are difficult to formulate because. of the differences in the profit potentials of the various outlets. Differences in measured contribution margins among outlets may be explained by differences in the characteristics of the locations and facilities of the outlets as well as the differences in the performance of the outlet managers. Since the location and facilities of an outlet are not controllable by the outlet manager, the effects of these environmental factors should be extracted before evaluating the performance of the manager. For a small number of outlets, central marketing officials can be familiar with the potentials of the outlets and can subjectively adjust for the potential differences. However, for a larger number of outlets, subjective adjustments for potential differences are not feasible. The performance measurement and evaluation system proposed here extends responsibility accounting to make objective intraperiod performance standards valid and operational. The extended system incorporates statistical techniques to provide a means for estimating the effects upon an outlet's measured performance' of the nonmanagerial environmental factors associated with an outlet. Since these environmental factors are not controllable by the outlet manager, they can be eliminated and the manager held responsible only for the effects of those factors controllable by him.